Political Economy of Import Waste Regulations in East Java: Implications of Indonesia's Role as Waste Importer Country - Maria Indira Aryani; Aldira Mara Ditta Caesar Purwanto (Nusantara Science and Technology Proceedings, 2020)
Waste management is a significant problem faced by the world on a global scale. Globally, the People's Republic of China (PRC) is the country with the most extensive waste trade in the world as the leading export destination country for recycled waste materials. However, the PRC changed its solid waste import policy by issuing a National Sword policy, which aims to limit and tighten plastic waste imports. The PRC policy change's impact is the increased flow of waste imports to Indonesia, thus placing Indonesia in a "Plastic Waste Emergency" situation. Since 2018, Indonesia's flow of waste imports has increased very rapidly, causing various environmental and health problems. On the other hand, waste imports entering Indonesia also open up various opportunities for economic improvement. This research then aims to find that the import of waste has an impact not only in the environmental sector but also on the political economy resulting from the government's efforts to overcome it. To overcome this problem, Indonesia already has several regulations and laws related to importing waste. Lack of strict import waste regulations has resulted in environmental and health losses for local communities in East Java. This research tries to describe various consequences of waste that would potentially harm citizens regarding waste using the role theory approach.